'Ignoring me is part of learning': Supervisory feedback on doctoral writing. Issue 1 (2nd January 2017) - Carter, Susan; Kumar, Vijay
Abstract: Doctoral supervisors aim for two goals. One is a strong thesis, timely in submission. The other is the fully fledged independent researcher who is able to write about research clearly within an epistemologically accepted framework. Feedback and feedforward on writing should address both goals. However, in many institutions, supervisors are under pressure towards the timely completion of the thesis, and urgency can easily over-ride the development of a researcher with a full set of academic competencies. There is also tension between the high emotional response from students receiving writing feedback and their desire for honesty from supervisors. Feedback may demotivate students to the degree that supervisors hesitate to give rigorous feedback. Data from interviews [n11] and anonymous questionnaires [n226] illuminate the tensions affecting the reality of supervisory writing feedback; in response, we suggest ways that supervisory discussion might accomplish the two goals of timely output and independent research writer.